Makna Dzikir dalam Perspektif Tafsir Sya’rāwī (Studi Analisis terhadap Tafsir Surat Al-Ra’d ayat 28) - Misbakhul Khaer (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2021)
The exploration of the meaning behind the Qur'anic text carried out by the mujtahids (mufasir) from the classical period to the present seems to continue to show its stretching. One of them is Imam Asy Sya'rÄwÄ«, a scholar who lived in the 20th century who tried to understand the Quran from the side of Sociological Education (al-Adab al-IjtimÄ`Ä«). This paper will unravel one of his interpretations and discuss the meaning of serenity that comes from dhikr through the interpretation of the letter al-Ra`Äd: 28. Imam Sya'rÄwÄ« said that the tranquility that arises because of dhikr is conditional. The first condition is to fully believe in the provisions (destiny) of Allah and the second condition is to have total trust in Him. By referring to the diversity of meanings of dhikr, Sheikh Sya'rÄwÄ« argues that dhikr in verse 28 of surah al-Ra`Äd means the Qur'an because every verse that comes from the Qur'an calms the heart of the Prophet Muhammad. His peace of mind is getting stronger because it is supported by his strong faith. As a conclusion to the interpretation of verse 28 of Surah al-Ra`Äd, Sheikh Sya'rÄwÄ« reveals the doubts that befell some orientalists who allege there is a contradiction between the substance of Surah al-Ra`Äd: 28 and Surah al-AnfÄl: 2 In Surah al-Ra`Äd verse 28 it is said that dhikr has the effect of feeling calm and comfortable, while in Surah al-AnfÄl verse 2 it is not so, dhikr actually causes fear. Faced with this accusation, Imam al-Sha'rÄwÄ« replied, that if the orientalists really understood the uslÅ«b (composition) and the characteristics of the Arabic language, they would have known the difference between the two verses which they considered contradictory.